Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.11138/gchir/2015.36.6.276
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular mucocele: two case reports and literature review

Abstract: L.R., a 45-years-old woman, Caucasian race. Past medical history: tonsillectomy in childhood; Laparoscopic cholecystectomy in 1993; in 2004 ATC-HCV positivity (transaminases always remained normal and HCV-RNA quantitative research always negative). Menarche at 12 years; regular menstrual cycles; abortion 18 years; abortion 36 years for fetal genetic disease; then subsequent pregnancy terminated in the first quarter; 3 attempts at artificial insemination with ovarian stimulation, without success.She comes to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…While appendiceal tumors comprise only a small percentage of gastrointestinal neoplasms, the subclassification of low-grade appendiceal mucinous neoplasm (LAMN) is even rarer by comparison. LAMNs are three times more likely to affect females than males and are typically found in patients between the ages of 50-60 years [3,4]. The clinical presentation of an appendiceal neoplasm varies greatly for both men and women, making it difficult to diagnose on initial presentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While appendiceal tumors comprise only a small percentage of gastrointestinal neoplasms, the subclassification of low-grade appendiceal mucinous neoplasm (LAMN) is even rarer by comparison. LAMNs are three times more likely to affect females than males and are typically found in patients between the ages of 50-60 years [3,4]. The clinical presentation of an appendiceal neoplasm varies greatly for both men and women, making it difficult to diagnose on initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients remain asymptomatic, while others present with weight loss, hematochezia, bowel obstruction, or bowel perforation, which may be signs of advanced disease. Because of this spectrum of possible presentations, LAMNs result in broad differentials and can be mistaken for various pathologies such as appendiceal diverticulitis or endometriosis [4,5]. It is also important to note that nearly a quarter of patients present without symptoms, and therefore are diagnosed with a LAMN based on an incidental finding [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative diagnosis of mucinous tumors is rare because of the low incidence of these tumors, the nonspecific symptoms and the relatively few significant biochemical parameters and imaging findings. [20] Ultrasound and abdominal and pelvic CT can be useful to identify swelling in the right iliac fossa or thickening of the wall of the cecum, but these findings may be common with other diseases, such as adenocarcinoma of the cecum, Crohn's disease, or ileocolonic intussusception. Thus, these findings are not conducive to the early detection and treatment of MAC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these findings are not conducive to the early detection and treatment of MAC. [20,21] It has been reported that endoscopic ultrasound (EUS) has a unique advantage for the diagnosis of MAC associated with ascites; EUS frequently identifies ascites missed by other imaging studies, including abdominal CT. This study also demonstrated that EUS-guided paracentesis could identify malignancy in ascetic patients.…”
Section: Discussionmentioning
confidence: 99%